Mendongeng sebagai Metode Dakwah Edukatif Pembentuk Karakter Islami Anak - Anwar, Rully Khairul; Rukmana, Evi Nursanti; Saepudin, Encang (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
This study examines the role of storytelling as an educational da'wah method in forming Islamic characters in children. In the context of character education, which is becoming increasingly important, the method of storytelling is considered to have great potential in conveying religious and moral messages to children interestingly and effectively. This study used a descriptive, qualitative approach by collecting data through surveys, document analysis, interviews, and observations at the Community Book Corner Pabukon Ngadongeng. Results showed that storytelling improves children's religious and moral understanding. Analysis of the documents also revealed variations of Islamic storytelling themes relevant to Islamic character values. Storytellers and educators play an essential role in this community book corner in selecting appropriate story material for children's age and understanding. Storytelling can potentially shape children's Islamic character through interactive and engaging educational dakwah. This study provides educators, preachers, and parents with a guide for using storytelling as an essential tool for Islamic character education for the younger generation.